Empowerment through education: the case of adult African refugees - Hiegemann, Valentina (AUC Knowledge Fountain, 2013)
While much of the existing information on the education of African refugees in Egypt has focused on children, this study reveals critical issues regarding the education of adults. This thesis has three major purposes. It aims to explore the different educational opportunities available for adult African refugees in Cairo. It seeks to examine the challenges that affect their education. It also analyzes the role of education in the empowerment of adult African refugees who either seek to integrate locally, return to their home country, or get resettled to another state. Research for this study was conducted over a period of three months in the city of Cairo. Substantial information was obtained from interviews with 30 adult students of two major refugee educational programs and four representatives from different organizations and institutions. On the basis of the results of this research, it can be concluded that due to the lack of access to formal education, the only educational opportunity available for the majority of adult African refugees is English classes provided by alternative refugee educational programs. It can also be concluded that many of the restrictions and obstacles faced by African refugees in Cairo have a negative effect on their education. Findings reveal that education, particularly English knowledge, significantly empowers adult refugees. One of the most significant results of this study is that education showed to be a powerful tool in improving the situation of many of the refugees residing in Cairo.